2017
DOI: 10.1083/jcb.201608104
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial virulence factors VopL and VopF nucleate actin from the pointed end

Abstract: How the bacterial virulence factors VopL/F from Vibrio catalyze actin nucleation is unclear. Using multicolor TIRF microscopy imaging, Burke et al. find that VopL and VopF stimulate actin assembly via identical pointed-end nucleation mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…Finally, VopL and VopF are bacterial tandem WH2-domain-containing actin assembly factors of the Spire type, which support the colonization of infected epithelia by Vibrio parahaemolyticus (Liverman et al, 2007) and Vibrio cholerae (Tam et al, 2007), respectively. Although these proteins bind to both barbed and pointed actin filament ends (Pernier et al, 2013), nucleation was recently found to mostly occur from the pointed end (Burke et al, 2017).…”
Section: The Regulation Of Cell Edge Protrusions: Lamellipodia and Fimentioning
confidence: 99%
“…Finally, VopL and VopF are bacterial tandem WH2-domain-containing actin assembly factors of the Spire type, which support the colonization of infected epithelia by Vibrio parahaemolyticus (Liverman et al, 2007) and Vibrio cholerae (Tam et al, 2007), respectively. Although these proteins bind to both barbed and pointed actin filament ends (Pernier et al, 2013), nucleation was recently found to mostly occur from the pointed end (Burke et al, 2017).…”
Section: The Regulation Of Cell Edge Protrusions: Lamellipodia and Fimentioning
confidence: 99%
“…The crosslinker protein α-actinin-1, both in unlabeled form and tagged with mCherry, was purified as described in Ciobanasu et al (2014). Capping protein (CP) was purified as described (Burke et al, 2017), with minor modifications. From the elution buffer, the protein was dialyzed into phosphate-buffered saline (PBS) and labeled with SNAP-surface Alexa Fluor 647 following the manufacturer's protocol (New England Biolabs).…”
Section: Protein Preparationmentioning
confidence: 99%
“…Possibly, Spir only binds barbed ends in the presence of actin monomers as was described for N-Wasp (Co et al, 2007). This contrasts with VopL/F that primarily bind barbed ends of preformed filaments in the absence of free monomer (Burke et al, 2017). The first of Spir's tandem WH2 domains, WH2-A, is necessary to cap barbed ends.…”
Section: Spir Binds Both Ends Of Actin Filamentsmentioning
confidence: 94%
“…To our surprise, we found that SpirNT-beads were sufficient to bind both ends of actin filaments. There are conflicting reports regarding filament-end binding for two classes of tandem-WH2 nucleators: Spir and VopF/L (Liverman et al, 2007;Yu et al, 2011;Pernier et al, 2013Pernier et al, , 2016Burke et al, 2017). The N-termini of WH2 domains bind actin monomers between subdomains 1 and 3 of actin -the surface exposed at the barbed ends of filaments (Chereau et al, 2005;Hertzog et al, 2004).…”
Section: Spir Binds Both Ends Of Actin Filamentsmentioning
confidence: 99%
See 1 more Smart Citation